2016
DOI: 10.1080/0886022x.2016.1227919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective effect of agmatine against cisplatin nephrotoxicity with 99mTc-DMSA renal scintigraphy and cystatin-C

Abstract: Our data indicate that AGM has a protective effect against cisplatin-induced nephrotoxicity. Therefore, it may improve the therapeutic index of cisplatin. In addition, the early renal damage induced by cisplatin and protective effects of AGM against cisplatin nephrotoxicity was accurately demonstrated with 99mTc-DMSA renal scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Another report also noted that a single i.p. dose of 7.5 mg/kg CDDP significantly elevated renal toxicity biomarkers level and caused remarkable damage to glomerular and tubular structures [35] . Additionally, Dirican et al in 2016 noted that serum cystatin-c and lipocalin-2 levels were markedly elevated in rats treated with a single i.p.…”
Section: Discussionmentioning
confidence: 96%
“…Another report also noted that a single i.p. dose of 7.5 mg/kg CDDP significantly elevated renal toxicity biomarkers level and caused remarkable damage to glomerular and tubular structures [35] . Additionally, Dirican et al in 2016 noted that serum cystatin-c and lipocalin-2 levels were markedly elevated in rats treated with a single i.p.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that 99m Tc-DMSA static renal scintigraphy is a sensitive and reliable test for the early detection of the kidney damage. 25,26…”
Section: Introductionmentioning
confidence: 99%
“…There was no correlation among the level of Cystatin C after the cisplatin infusion and serum creatinine level following the third course and modification of diet in renal disease and creatinine clearance-Cockcroft-Gault formulations 39 . Previous studies have also used serum Cystatin C levels to evaluate that agma-tine has a protective effect against cisplatininduced nephrotoxicity 40 .…”
Section: Renalmentioning
confidence: 99%